Viral and Bacterial Etiologies of Acute Respiratory Infections Among Children Under 5 Years in Senegal. (13th February 2018) - Assane, Dieng; Makhtar, Camara; Abdoulaye, Diop; Amary, Fall; Djibril, Boiro; Amadou, Diop; Niokhor, Diouf Jean Baptiste; Amadou, Diop; Cheikh, Loucoubar; Ndongo, Dia; Mbayame, Niang; Lamine, Fall; et al.
Acute respiratory infections (ARIs) are the leading cause of infectious disease–related morbidity, hospitalization, and morbidity among children worldwide. This study aimed to assess the viral and bacterial causes of ARI morbidity and mortality in children under 5 years in Senegal. Nasopharyngeal samples were collected from children under 5 years who had ARI. Viruses and bacteria were identified using multiplex real-time reverse transcription-polymerase chain reaction and conventional biochemical techniques, respectively. Adenovirus was the most prevalent virus (50%; n = 81), followed by influenza virus (45.68%, n = 74), rhinovirus (40.12%; n = 65), enterovirus (25.31%; n = 41), and respiratory syncytial virus (16.05%; n = 26), whereas Streptococcus pneumoniae (17%; n = 29), Moraxella catarrhalis (15.43%; n = 25), and Haemophilus influenzae (8.02%; n = 13) were the most commonly isolated bacteria. Virus pathogens seem more likely to be more prevalent in our settings and were often associated with bacteria and S. pneumoniae (6%; 16) coinfection.